How national policies influence energy community development across Europe? A review on societal, technical, and economical factors - G.U. Magni; F. Battistelli; F. Trovalusci; D. Groppi; D. Astiaso Garcia (Energy Conversion and Management: X, 2024)
Renewable Energy Communities (RECs) have been clearly defined in the EU Renewable Energy Directive (RED) II (Directive 2018/2001) contained within the Clean Energy Package (CEP). This review moves from the state of the art of transposition processes in place in the different EU member states in order to highlight the main barriers regarding actual implementation of RECs, in terms of governance, technical issues and economic sustainability. The paper analyses the three levels of the structure of any REC: the social and governance level, the energy and technology optimization aspects, and the business models. The analysis has been conducted by considering the models developed in literature and the most interesting case studies where these models have been applied. The work aims at finding some conclusions about the interactions between the three levels mentioned above and national policy regulations, while identifying gaps in the currently available literature.